2022
DOI: 10.3389/fphys.2021.766346
|View full text |Cite
|
Sign up to set email alerts
|

Time to Move Beyond a “One-Size Fits All” Approach to Inspiratory Muscle Training

Abstract: Inspiratory muscle training (IMT) has been studied as a rehabilitation tool and ergogenic aid in clinical, athletic, and healthy populations. This technique aims to improve respiratory muscle strength and endurance, which has been seen to enhance respiratory pressure generation, respiratory muscle weakness, exercise capacity, and quality of life. However, the effects of IMT have been discrepant between populations, with some studies showing improvements with IMT and others not. This may be due to the use of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 114 publications
1
18
0
1
Order By: Relevance
“…Previous RCTs in obese adults (15)(16)(17)40) that reported substantial benefit after threshold IMT all commented on the importance of periodic adjustment of the training load to yield optimal training outcomes. Concerning other useful recommendations for improving respiratory muscles in clinical practice, Shei et al (12) recommended that the training session be personalized, and to consider setting training goals, such as improving RMS and/or endurance, to facilitate longer training sessions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous RCTs in obese adults (15)(16)(17)40) that reported substantial benefit after threshold IMT all commented on the importance of periodic adjustment of the training load to yield optimal training outcomes. Concerning other useful recommendations for improving respiratory muscles in clinical practice, Shei et al (12) recommended that the training session be personalized, and to consider setting training goals, such as improving RMS and/or endurance, to facilitate longer training sessions.…”
Section: Resultsmentioning
confidence: 99%
“…The other study found significant improvement in 6-MWT distance after IS training ( 18 ). The mechanism of increased RMS after IMT may be multifactorial ( 12 ). The proposed mechanisms include increased proportion and size of type II muscle fibers ( 16 , 41 , 42 ), promoted diaphragm hypertrophy, attenuated respiratory muscle metaboreflex, and enhanced respiratory muscle economy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El entrenamiento de los músculos inspiratorios (inspiratory muscle training, IMT) es una herramienta de rehabilitación que ayuda a mejorar la fuerza y la resistencia de los músculos respiratorios, así como la capacidad de ejercicio funcional y la calidad de vida. Los dispositivos utilizados para IMT incluyen dispositivos de carga basados en presión (Threshold IMT) y volumen (espirómetro de incen-tivo (incentive spirometer, IS)), el más utilizado en la actualidad son los dispositivos de carga basado en presión [4].Existe mucha información sobre IMT en pacientes adultos con obesidad con buenos resultados en la función pulmonar, en población pediátrica se usa el IMT en otras enfermedades no relacionadas con la obesidad. De ahí la importancia de este artículo, porque el IMT podría ser otra herramienta más para que nuestros niños obesos puedan reincorporarse a la actividad física regular, al mejora la función y resistencia de los músculos respiratorios y la tolerancia al ejercicio.…”
Section: Contexto Del Estudiounclassified